Chemical–biological approaches for the direct regulation of cell–cell aggregation. Issue 2 (20th January 2022) - Ma, Jia‐Yi; Wang, Ya‐Xin; Huang, Yan; Zhang, Yi; Cui, Yun‐Xi; Kong, De‐Ming
Abstract: Cell–cell aggregation is one of the most well‐known modes of intercellular communication. The aggregation also plays a vital role in the formation of multicellularity, thus manipulating the growth and development of organisms. In the past decades, cell–cell aggregation‐related bioprocesses and molecular mechanisms have attracted enormous interest from scientists in biology, and bioengineering. People have developed a series of strategies to artificially regulate cell–cell aggregation through chemical–biological approaches. To date, not only the chemical reagents such as coordination compounds and polymers but also the biomacromolecules such as proteins and nucleic acids, are employed as the "cell glue" to achieve the control of the cell aggregation. So it is meaningful to review the recent advances of the chemical–biological approaches in cell–cell aggregation manipulation. In this review, we discuss the mechanisms and features of recently developed strategies to control cell–cell aggregation. We introduce molecules and designs relying on chemical reactions and biological conjugations respectively, and talk about their advantages and suitable applications. A perspective on the challenges in future applications in cell manipulation and cell‐based therapy is also proposed. We expect this review could inspire innovative work on manipulating cell–cell aggregation and further modulate cell–cell interactions in the research of bio/chemical fields. Abstract : The precise control of cell–cell aggregation is not only vital for the cell biological field but also important for bioengineering field. In this review, we summarize the recent strategies using chemical and biological molecules to achieve the programmable regulation of cell–cell aggregations. We discuss the advantage and disadvantage of recent approaches, and talk about the possible development of the technology in this filed in future.